Modelling and assessments of the physical ergonomics on the Accident & Emergency Department At Malaysian Hospital - Rohayu Othman (2020)
This study concerns about risk of work-related musculoskeletal disorder at existing Accident and Emergency Department of Malaysia Hospital due to load, postures and environments. The study is conducted at six Accidents and Emergency Department of Malaysia tertiary hospitals. The study has three objectives which are to determine the risk factors of work related musculoskeletal disorder of the existing Accident and Emergency Department through ergonomic workplace assessment, to model the relationship of work related musculoskeletal disorder among healthcare personnel with the risk factors of physical ergonomics and to determine the correlation and significant effect between risk factors of work related musculoskeletal disorder with physical ergonomics at Accident and Emergency Department. The study used two methods, which are questionnaire and workplace assessment. The respondents to answer the questionnaire are medical doctors, medical assistants and nurses. Data collected from the questionnaire are analyzed using SPSS and the hypotheses are tested using structural equation modeling (SEM). As for workplace assessment, observations are made at red zone. During the observation period, the condition at red zone is evaluated such as the load, posture and environment. Rapid entire body assessment (REBA) is chosen for postures assessment. Results from questionnaire proved that load and postures have significant effect on work related musculoskeletal disorder. However, according to result from questionnaire, environment does not have a positive impact to work related musculoskeletal disorder. Finding from workplace assessments shows similar findings that suggested loads and postures contribute to the risk of musculoskeletal disorder at workplace. Workplace assessment, however, suggested that, environment contribute to the risk of musculoskeletal disorder at red zone of Malaysia Accident and Emergency Department. Findings from this study can contribute to the development or improvement of any Red Zone specifically, and Accidents and Emergency Department as a whole, that will have reduced impact of work-related musculoskeletal disorder to the healthcare workers.